The Interplay of social media and English Proficiency of Indonesian University Students’ Exchange - Andi Sadapotto; Nadirah; Muthmainnah; Muhammad Hanafi; Anugrah Yuda Pratama (UNIB Press, 2023)
This research uses the descriptive qualitative method as the research methodology. This research was conducted to know what is the most common social media influence student’s English-Speaking ability and how does social media influence student English speaking ability. The population in this research were the students of Pertukaran Mahasiswa Merdeka Inbound State University of Malang in this research were 10 students. The data collection method used in this research was an interview. The results shown that the most social media that influence students to improve their speaking ability is YouTube. Social can influence the students to improve their speaking ability because in social media there are so many contents that provide them to learn English especially to improve their speaking ability such as video, picture, photo, etc.